Professionalization of controllers in Finland - Vuonnala, Riikka (My University, 2013)
Professions are a special category of occupations that possesses exclusive rights over its domain of expertise. Professions apply expert knowledge in their work by using professional discretion and judgment to solve their clients’ problems. With control over their expert knowledge base, professions are able to control the supply of practitioners in their field and regulate the practice in their market. Professionalization is the process during which occupations attempt to gain the status of a profession. The benefits of becoming a profession are extensive – professional autonomy, social and financial rewards, prestige, status, and an exclusive community are only a few of the privileges that established professions possess. Many aspiring occupations have tried and failed to gain the status of a profession and one of these groups is the occupation of controllers in Finland. The objective of this study to uncover, why controllers have not professionalized, which properties of the occupation correspond with the elements generally regarded to pertain to professions, and which aspects of the occupational group may hinder the professionalization project. The professionalization project of controllers is analyzed using a multi-actor model of professionalization, in which practitioners, clients, the state, training institutions, and employing organizations are considered to affect the project. The properties of the occupation of controllers are compared to features generally associated with professions. The research methodology for this thesis is qualitative, and the study is conducted as an exploratory research. The data is primarily gathered using semi-structured interviews, which were conducted between March and May 2013 lasting from 40 minutes to an hour. In total, four controllers were interviewed, who worked for different companies operating in different industries, and whose experience of working as a controller varied between a few years to nearly 15 years. The data in this study indicates that although controllers possess qualities that distinguish professions from other occupational groups, the professionalization of controllers may not be plausible. Controllers enjoy considerable autonomy in organizations, and they possess a strong orientation towards serving their clients. The more profound problem with the occupation is its non-exclusive, indistinct knowledge base that does not rely solely on a single knowledge base. Controllers’ expertise is relatively organization-specific and built on several different fields of knowledge and not just management accounting, which could be considered as their primary knowledge base. In addition, controllers have not organized themselves, which is a quintessential, but by no means a sufficient prerequisite for professionalization.